Hybridism as a Dualistic View, or: A “Latourian” Paradox - Pellegrino, Gianfranco (E|C, 2023)
Hybridism is the view that there are no purely natural or cultural, social or artificial objects, and the distinction between nature and culture/society/artifice is ungrounded and epistemologically impossible. Hybridism is usually taken as an anti dualist view. The paper challenges this claim. It provides a taxonomy of hybridism(s). The main claim of the paper is that hybrids, in the best understanding of them, are still dual(ist). However, the esidual, or surviving, dualism embedded in hybridism has stronger grounds than the traditional Cartesian dualisms. As a consequence, the paper is also a defense of a moderate dualist view of nature and society, nature and culture, and nature and artifice. These claims are defended also by giving an interpretation of (some of) Latour s views about hybrids, mainly resting on a view of Latourian hybrids i.e., of the specific things, events, or phenomena that Latour saw as hybrids in (some of) his works.